Systematic evaluation of the early access applied biosystems precision ID Globalfiler mixture ID and Globalfiler NGS STR panels for the ion S5 system. (September 2018) - Müller, Petra; Alonso, Antonio; Barrio, Pedro A.; Berger, Burkhard; Bodner, Martin; Martin, Pablo; Parson, Walther; ,
Highlights: Inter-laboratory evaluation of two early access Globalfiler MPS panels with respect to STR performance. We assessed concordance, sensitivity and casework samples (including mixtures). Our study indicates that the early access Globalfiler MPS panels are powerful tools with benefits for practical forensic casework.